Sistem Informasi Klinik Hewan Untuk Meningkatkan Kinerja Keuangan Menggunakan Metode Rasio Profitabilitas - Taufik Kurnialensya (Ultimatics : Jurnal Teknik Informatika, 2021)
Veterinary Clinic which is located at Jalan Brigjend. S. Sudiarto No. 134 Semarang is an agency engaged in serving its clients in caring for the health of livestock and pets. In recording and processing data using an organized system and not yet well integrated. In financial management and also in making financial reports, it is not optimal in evaluating financial performance, so that they cannot see the ability to generate operating profit from the income generated. There is a need for a system to be used to increase activity at the veterinary clinic, so that it is much more effective and efficient in the provision of equipment, equipment, and data management including recording, making financial reports, and assessing financial performance, so that it can show the time used and the system as well. can be accessed simultaneously by interested parties. In the implementation of a new system, namely the Animal Clinic Information System to Improve Financial Performance with the Web-Based Ratio method. From these problems, an application program can be made using PHP and MySQL as the database. With the above design, it provides benefits for veterinary clinics that provide benefits in improving their financial performance, can be accessed simultaneously, and provides services in the provision of equipment and equipment needed.